Unexpected Decrease in Shunt Surgeries Performed during the Shelter-in-Place Period of the COVID-19 Pandemic. Issue 5 (11th January 2021) - Laxpati, Nealen; Bray, David P; Wheelus, Jennifer; Hamilton, Kimberly; Boydston, William; Reisner, Andrew; Sawvel, Michael; Chern, Joshua J
Abstract: BACKGROUND: It is expected that the incidence of cerebrospinal fluid (CSF) shunt malfunctions would remain unchanged during the shelter-in-place period related to the COVID-19 pandemic. OBJECTIVE: To examine the number of shunt surgeries performed in a single institution during this time interval in comparison to equivalent periods in past years. METHODS: The numbers of elective and emergent/urgent shunt surgeries performed at a single institution were queried for a 28-d period starting on the third Monday of March, between years 2015 and 2020. These were further stratified by how they presented as well as the type of surgery performed. RESULTS: During the 28-d period of interest, in the years between 2015 and 2020, there was a steady increase in the number of shunt surgeries performed, with a maximum of 64 shunt surgeries performed in 2019. Of these, approximately 50% presented in urgent fashion in any given year. In the 4-wk period starting March 16, 2020, a total of 32 shunt surgeries were performed, with 15 of those cases presenting from the outpatient setting in emergent/urgent fashion. For the surgeries performed, there was a statistically significant decrease in the number of revision shunt surgeries performed. CONCLUSION: During the 2020 COVID-19 pandemic, there was an unexpected decrease in the number of shunt surgeries performed, and particularly in the number of revision surgeries performed. This suggests that an environmental factor related to the pandemic is altering the presentation rate of shunt malfunctions.